Exploring geographic distributions of high-risk water, sanitation, and hygiene practices and their association with child diarrhea in Uganda. Issue 1 (1st December 2016) - Hirai, Mitsuaki; Roess, Amira; Huang, Cheng; Graham, Jay
Abstract : Background: High-risk water, sanitation, and hygiene (WASH) practices are still prevalent in most low-income countries. Because of limited access to WASH, children may be put at an increased risk of diarrheal diseases. Objectives: This study aims to 1) develop a new measure of WASH-induced burden, the WASH Resource Index (WRI), and estimate its correlation with child diarrhea and an additive index of high-risk WASH practices; 2) explore the geographic distribution of high-risk WASH practices, child diarrhea, and summary indices at the cluster level; and 3) examine the association between the WRI and child diarrhea at the individual level. Design: A sample of 7, 019 children from the Uganda Demographic and Health Survey 2011 were included in this study. Principal component analysis was used to develop a WRI, and households were classified as WASH poorest, poorer, middle, richer, and richest. A hot spot analysis was conducted to assess whether and how high-risk WASH practices and child diarrhea were geographically clustered. A potential association between the WRI and child diarrhea was examined through a nested regression analysis. Results: High-risk WASH practices were clustered at geographically distant regions from Kampala. The 2-week prevalence of child diarrhea, however, was concentrated in Eastern and East Central regions where high-risk WASH practices were not prevalent. At the individual level, none of the high-risk WASH practices were significantly associated with child diarrhea. Being in the highest WASH quintile was, however, significantly associated with 24.9% lower prevalence of child diarrhea compared to being in the lowest quintile ( p <0.05). Conclusions: Only a weak association was found between the WRI and child diarrhea in this study. Future research should explore the potential utility of the WRI to examine WASH-induced burden.